Intensidade de jogos oficiais de futsal - Vinicius de Matos Rodrigues (2008)
The purpose of the present study was to identify the intensity of official futsal games.Fourteen male professional players of the adult category (>20 years) were evaluated.They belonged to a futsal team that keeps regular training and participation incompetitions recognized by the Brazilian Confederation of Futsal. The maximumoxygen uptake (VO2max) and the relation between heart rate (HR) and oxygen uptake(VO2) for each player were determined twice throughout the study (before and aftercompetition). The intensity of the games was estimated by the HR of the playersrecorded during thirteen games of the Futsal League, having been eight games of thefirst phase (April, May, June and July) and five games of the second phase (Augustand September). HR was registered by a set of HR monitors. Later these values ofHR were used to express the intensity in percentage of the HRmax (%HRmax),percentage of the VO2max (%VO2max), kilocalories per minute (kcal.min-1) and multiplesof the basal metabolic rate (MET). To determine the intensity of the games, only theHR values recorded when the athletes were in the game court were considered, beingdiscarded, the HR records at the moments when the athletes were sitting out. Theaverage intensity of the games was 86.4 ± 3.8% HRmax, that corresponded to 79.2 ±9.0 %VOmax, 18.0 ± 2.2 kcal.min-1 and 15.9 ± 1.5 MET. We concluded that the officialgames of futsal are of high intensity